Aqueous alteration detection in Tikhonravov crater, Mars. (March 2018) - Mancarella, F.; Fonti, S.; Alemanno, G.; Orofino, V.; Blanco, A.
Abstract: The existence of a wet period lasting long enough to allow the development of elementary forms of life on Mars has always been a very interesting issue. Given this perspective, the research for geological markers of such occurrences has been continually pursued. Once a favorable site is detected, effort should be spent to get as much information as possible aimed at a precise assessment of the genesis and evolution of the areas showing the selected markers. In this work, we discuss the recent finding of possible deposits pointing to the past existence of liquid water in Tikhonravov crater located in Arabia Terra. Comparison of CRISM spectra and those of laboratory minerals formed by aqueous alteration has led us to the conclusion that the studied areas within the impact crater host phyllosilicates deposits. In addition, analysis of the CRISM spectra has resulted in the tentative identification of carbonates mixed with phyllosilicates. Highlights: We found deposits pointing to the past presence of water in Tikhonravov crater, Mars. We analyzed two CRISM observations in the deepest minor impact crater. The areas within the impact crater host phyllosilicates deposits. A more accurate inspection has resulted in possible identification of carbonates.